Meat species identification and Halal authentication analysis using mitochondrial DNA - Lesley Maurice, Bilung; Chandrika, Murugaiah; Zainon, Mohd Noor; Maimunah, Mustakim; Jinap, Selamat; Son, Radu (Elsevier Science, Ltd., 2009)
A method utilizing PCR-restriction fragment length polymorphism (RFLP) in the mitochondrial genes was developed for beef (Bos taurus), pork (Sus scrofa), buffalo (Bubalus bubali), quail (Coturnix coturnix), chicken (Gallus gallus), goat (Capra hircus), rabbit (Oryctolagus cuniculus) species identification and Halal authentication. PCR products of 359-bp were successfully obtained from the cyt b gene of these six meats. AluI, BsaJI, RsaI, MseI, and BstUI enzymes were identified as potential restriction endonucleases to differentiate the meats. The genetic differences within the cyt b gene among the meat were successfully confirmed by PCR-RFLP. A reliable typing scheme of species which revealed the genetic differences among the species was developed